2013
DOI: 10.1093/alcalc/agt052
|View full text |Cite
|
Sign up to set email alerts
|

The Alcohol Improvement Programme: Evaluation of an Initiative to Address Alcohol-Related Health Harm in England

Abstract: Aims: The evaluation aimed to assess the impact of The Alcohol Improvement Programme (AIP). This was a UK Department of Health initiative (April 2008–March 2011) aiming to contribute to the reduction of alcohol-related harm as measured by a reduction in the rate of increase in alcohol-related hospital admissions (ARHAs). Methods: The evaluation (March 2010–September 2011) used a mix of qualitative and quantitative methods to assess the impact of the AIP on ARHAs, to describe and assess the process of implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…There has been considerable recent growth in the number of AHWs in England (Thom et al, 2013). Previous work by two of this paperÕs authors established the extent of AHW provision at a national level through a survey of 48 hospitals in England that showed 45 of these had at least one AHW (Baker et al, 2014).…”
Section: Previous Researchmentioning
confidence: 98%
“…There has been considerable recent growth in the number of AHWs in England (Thom et al, 2013). Previous work by two of this paperÕs authors established the extent of AHW provision at a national level through a survey of 48 hospitals in England that showed 45 of these had at least one AHW (Baker et al, 2014).…”
Section: Previous Researchmentioning
confidence: 98%
“…The information can be re-passed verbally to the users of the services as well to the mutual help groups. Iran 15,40 , USA 23 , Thailand 18 , Switzerland 24 , India 29 , England 35,41 , Tanzania 32 and China 38 adopted informative interventions associated with other HR services. The preventative information can also be spread through printed material that usually accompany the supplies which is the case with the syringes, pipes and HR kits offered in the experiences in Brazil 4,21,32 and in Tanzania 42 .…”
Section: Information and Counselingmentioning
confidence: 99%
“…The research reported draws on a full report submitted to the Department of Health (Thom et al, 2012) -and subsequent paper (Thom et al, 2013) which presented the findings and analysis from a two year project to evaluate the Alcohol Improvement Programme. This was an independent project…”
Section: Acknowledgementsmentioning
confidence: 99%